40.7k views
0 votes
What will be the resulting equation when you substitute the first equation (-3x + 5) in for y in the second equation?

Equation 1: y=(-3x+5)
Equation 2: 5x-4(y)=-3

User Jamira
by
4.6k points

2 Answers

3 votes

Answer:

Step-by-step explanation:Substituting for y:

5x - 4(-3x + 5) = -3

5x + 12x - 20 = -3

17x = -3 + 20

17x = 17.

1

User Ponder Stibbons
by
5.4k points
4 votes

Answer:

See below.

Explanation:

Substituting for y:

5x - 4(-3x + 5) = -3

5x + 12x - 20 = -3

17x = -3 + 20

17x = 17.

x = 1.

User Taimur Aziz
by
4.7k points